Five supposedly well-known species of Leptogium section Mallotium - Kitaura, M. J. [UNESP]; Marcelli, M. P.; Jungbluth, P. [UNESP]; Hora, B. R. [UNESP] (Mycosphere Press, 2013)
The revision and detailed description of type specimens of five supposedly well-known hairy Leptogium species revealed taxonomically relevant new data. Both holotype and isotype of L. capense are a mixture of species and a new lectotype is designated. A new isotype of L. decipiens was found at E. The protologue of L. inversum mentioned marginal apothecia but the holotype has just laminal and sub-marginal apothecia. The lectotype duplicate of L. resupinans is not really a fragment of the lectotype and must be considered as syntype. The apothecia of L. scrobiculatum are described for the first time.
Keywords: Collemataceae; cylindrical cells; hairs; type material